A Stretchable and Transparent Electrode Based on PEGylated Silk Fibroin for In Vivo Dual-Modal Neural-Vascular Activity Probing - Cui, Yajing (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.